Legal protection of the right to privacy in light of technological development - Hamdi, Hakima; Goutal, Yacine (The International tax journal, 2026)
The right to privacy has been affected by technological development, which has a wide scope of use. Modern technology has become a new method of communication between individuals and a field for exchanging information and secrets. It later became clear that individuals’ data and information are vulnerable to dissemination and exploitation. Therefore, laws have been enacted to address these violations through the legislation of countries, as well as international and regional organizations, to confront modern electronic crimes imposed by technological development. Algeria, like many other countries, has faced electronic attacks on the right to privacy and combated electronic crime through its Penal Code and criminalized every violation of the right to privacy.